Chicago, Harvard, and the Doctrinal Foundations of Monetary Economics - Tavlas, George S. (Journal of Political Economy, 1997)
The relationship between Milton Friedman's monetary economics and the views espoused by Chicago and non-Chicago quantity theorists during the years 1930-36 is examined. Contrary to recent interpretations, Chicago economists advanced the efficacy of monetary policy as the means of escaping from the Great Depression, provided that such a policy was implemented by the use of budget deficits to generate monetary expansion. The use of the quantity theory of money to provide a theoretical rationale for budget deficits distinguished the Chicago economists from other quantity theorists and left them less susceptible to the Keynesian revolution. The claim that Harvard was an important center for monetary research in the early 1930s is refuted.